Analysis of methods for applying ceramic coatings in various ways to increase the operational stability and wear resistance of parts (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article discusses experimental studies of applying ceramic coatings by various methods and means to components of working bodies of agricultural machinery, engines of automobile and tractor machinery. In addition, several ceramic coating materials and their application processes were carefully considered, the use of ceramic coating optimization methods, as well as dispersion analysis were investigated.
Keywords: ceramic coatings; coating methods; engine performance; dispersion analysis; optimization; flame spraying; restoration; agricultural machinery; automotive; wear resistance